SYNTHESIS OF MANGANESE CLAY AS WATER FILTER MATERIAL OF KAHAYAN RIVER FOR ALTERNATIVE WATER SUPPLY IN KALIMANTAN TENGAH - Karelius (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
Manganese clay had been synthesized as a water filter in order to find out how the quality of water by using parameters such as pH, concentration of iron (Fe), TSS (Total Suspended Solid) and turbidity in the water of Kahayan River before and after filtering it. The first step of Synthesizing the manganese clay was done bycalcining the natural clayat700 ° C for 3 hours,then it was soaked by applying MnCl2 solution of 5 g / L at 60 ° C for 12 hour; the second phase that itwas washed in order to remove its chloride ions, after that, it was dried at 80 ° C for 3 hours, then it was soaked by applying KMnO4 solution with concentration of 5 g / L at 60 ° C for 24 hours, then the clay was washed. Other supporting filters which were also used in the filtration processes, namely sand and gravel. Based on the result findings, before filtering the water, its quality was pH 5.5;Fe concentration of 2.16 mg / L, TSS of 258 mg / L;and turbidity of 140 NTU. After filtering the water by using manganese clay, the quality of Kahayan water is qualified to the requirements of clean water as inPermenkes No. 907/Menkes/VII/2002, thatthe parameters pH is 6.5; Fe concentration of 2.16 mg / L TSS 108 mg / L;and turbidity of 11.97 NTU. It is suggested that manganese clay can be used as a water filter Kahayan river for the alternative water suppy in Kalimantan Tengah.